2020
DOI: 10.18632/aging.102973
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine in combination with low-dose cytarabine, aclarubicin and G-CSF tends to improve prognosis in elderly patients with high-risk AML

Abstract: INTRODUCTION Acute myeloid leukemia (AML) is a hematopoietic malignancy that affects all age groups, but predominantly occurs in the elderly with a median age of 65 years [1]. The prognosis of older patients is worse than younger patients because of higher degree of resistance to conventional chemotherapy, increased frequency of genetic mutations, decreased performance status (PS), comorbid conditions, and limited treatment options [2-5]. The complete remission (CR) rates for AML patients above 60 years that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…months (19) . The fact that case1 is in continuous CR for 16 months and the latter two cases have the short remission time may be related to complex karyotype, and high VAF value (20) .Case4 and case 7 both have complex karyotype including -5/5q-and/or -7/7q-chromosomal deletions and TP53 mutation with VAF>20%.. More cases are needed for further study for VAF of TP53 and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…months (19) . The fact that case1 is in continuous CR for 16 months and the latter two cases have the short remission time may be related to complex karyotype, and high VAF value (20) .Case4 and case 7 both have complex karyotype including -5/5q-and/or -7/7q-chromosomal deletions and TP53 mutation with VAF>20%.. More cases are needed for further study for VAF of TP53 and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA (gDNA) was extracted from the bone marrow aspirates of each patient using an Autopure extractor (Qiagen, Hilden, Germany). Targeted gene sequencing (TGS) was tested on the Illumina Platforms (Kapa Biosystems, Wilmington, MA, USA) as previously described ( 9 ). A total of 42 genes were contained in the TGS panel, including ASXL1 , BCOR , BCORL1 , CALR , CBL , CEBPA , CSF3R , DNMT3A , ETV6 , EZH2 , FLT3 , GATA2 , IDH1 , IDH2 , JAK2 , KIT , KRAS , MLL , MPL , NF1 , NPM1 , NRAS , PDGFRA , PHF6 , PIGA , PPM1D , PTPN11 , RAD21, RUNX1 , SETBP1 , SF3B1 , SH2B3 , SMC1A , SMC3 , SRSF2 , STAG2 , STAT3 , TET2 , TP53 , U2AF1 , WT1 , and ZRSR2 .…”
Section: Methodsmentioning
confidence: 99%
“…HMAs combined with CAG regimen [LDAC, aclarubicin and granulocyte colony-stimulating factor (G-CSF)] tends to improve the prognosis of older patients with high-risk AML [15] . In patients with R/R AML, it was observed that increased dosage of the conventional CAG regimen was more effective as salvage therapy [16] .…”
Section: Introductionmentioning
confidence: 99%